Flavonoids-rich extract of Aframomum melegueta (black pepper) improves antioxidant status and modulates aging process in lead-induced neurotoxic Drosophila melanogaster - Mohammed Sani Jaafaru (Eurasian Journal of Science and Engineering)
There are insufficient shreds of evidence to support the longevity benefits of Aframomum melegueta-derived flavonoids. The present study focused on the investigation of the activity of flavonoid-rich extract in the neurotoxic Drosophila melanogaster model, where behavioral, biochemical, and molecular procedures were conducted to evaluate the activities and expression of phase II antioxidants and age-related enzymes. The extract was administered to fruit flies at doses of 3 and 5 mg/g over a period of seven days with subsequent exposure to 0.1 µg/g diet lead oxide for an equivalent number of days. The flies were homogenized for bioassays. The expression and activities of the phase II antioxidant and age-related enzymes were determined using quantitative polymerase chain reaction (qPCR) to assess the oxidative and longevity effects of the extract. Enhancement in locomotor function and flies’ emergence were observed as the outcomes of behavioral assay. The extract also hindered the detrimental effects of Pb by increasing the activities and gene expression levels of catalase and superoxide dismutase with concurrent inhibition of AChE activity and expression in the toxic environment. These findings shed light on the mechanism through which the extract inhibits lead-induced toxicity in D. Melanogaster, which may have potential implications for human subjects.